Venous thromboembolic disease prophylaxis among general surgeons in Malaysia - Prasannan, Subhita; Liew, Ngoh Chin; Alif Gul, Yunus Gul (Elsevier, 2005)
Objective: The aim of this study was to analyse the current practice of venous thromboembolism (VTE) prophylaxis among general surgeons in Malaysia. Methods: A questionnaire survey was conducted among general surgeons attending the annual Malaysian College of Surgeons meeting in 2002. A total of 110 questionnaires were distributed to specialist-grade general surgeons with varying subspecialty interests. Results: Seventy-seven (70%) surgeons returned the questionnaire. Of these, 43% were of the opinion that VTE was as common in Asian patients as in the West. Selective VTE prophylaxis was used by 99% in their practice. The indications for use, in order of frequency, were: previous VTE disease, risk grading, prolonged surgery, obesity, malignancy and age. Low molecular weight heparin was the most common type of prophylaxis used. VTE-related morbidity was reported by 44 surgeons (57%) over the past year, and 39% of these cases were fatal. Conclusion: The high incidence of VTE-related complications indicates that the use of thromboprophylaxis is either insufficient or not matched to the level of risk. Updated guidelines on VTE prophylaxis should be used so that a standardized approach can ensure that patients receive adequate prophylaxis where indicated.